Estimation Fishing Season of Skipjack Tuna (Katsuwonus pelamis) Using Data on Catch Production at Kutaraja Oceanic Fishing Port Aceh Province - Hasugian, Juniori Hulkman; Brown, Arthur; Bustari, Bustari (Journal of Coastal and Ocean Sciences, 2023)
Kutaraja Ocean Fishing Port (PPS) is a fishing port that has various catch characteristics; one of the most dominant catches is skipjack tuna. The purpose of this study was to analyze the skipjack tuna catches per unit fishing effort (CPUE) and to estimate the skipjack tuna fishing season index at the Ocean Fishery Port of Kutaraja. This research was conducted in October 2021 at the Kutaraja Ocean Fishing Port using the survey method. The results of the study showed that skipjack tuna catches at the Samudera Kutaraja Fishing Port in 2016-2020 experienced quite significant fluctuations. In addition, the fishing effort is quite high so the catch of skipjack per fishing effort (CPUE) for the 2016-2020 periods has decreased. The highest CPUE value was in September 2018, namely 7.163 kg/unit, and the lowest was in January 2016, namely 483 kg/unit. In this study, it can be assumed that the peak season for skipjack tuna occurs in May, July, August, September, and October. The moderate season for skipjack tuna occurs in January, February, March, June, November, and December